Possible Role for Interleukin-5 in Asthma - Al-Rubaeyi, Yacoob Y.; Al-Haidary, Batool A.; Jasim, Wala'a E. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Asthma is an allergic disease characterized by airway obstruction as a result of cellular accumulation due to the liberation of certain mediators. Among those mediators are the cytokines such as IL-5. Patients & Methods: Interleukin-5 concentration has been estimated in 94 sera samples of Asthmatic patients in comparison with 41 non-asthmatic bronchitis as patient controls in addition to 30 apparent healthy control group using ELISA method.Results & Conclusions: There is highly significant elevation of IL-5 in the asthmatic cases in comparison with healthy controls (P< 0.001). We conclude that this cytokine may play the majorrole in asthmatic attack & it may be a good marker for the disease.